2018
DOI: 10.1186/s40779-018-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 90-day readmission in veterans with inflammatory bowel disease—Does post-discharge follow-up matter?

Abstract: BackgroundRepeat hospitalizations in veterans with inflammatory bowel disease (IBD) are understudied. The early readmission rate and potentially modifiable risk-factors for 90-day readmission in veterans with IBD were studied to avert avoidable readmissions.MethodsA retrospective cohort study was conducted using the data from veterans who were admitted to the Minneapolis VA Medical Center (MVMC) between January 1, 2007, and December 31, 2013, for an IBD-related problem. All-cause readmissions within 30 and 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Future quality improvement activities need to include standards for aftercare in the immediate post‐discharge period to reduce avoidable readmissions. In a study of repeat hospitalizations in veterans with IBD, lack of an elective follow‐up visit after discharge was an independent risk factor for 90‐day readmission . The UK IBD Audit did not include any process measures relating to early post‐discharge review.…”
Section: Discussionmentioning
confidence: 99%
“…Future quality improvement activities need to include standards for aftercare in the immediate post‐discharge period to reduce avoidable readmissions. In a study of repeat hospitalizations in veterans with IBD, lack of an elective follow‐up visit after discharge was an independent risk factor for 90‐day readmission . The UK IBD Audit did not include any process measures relating to early post‐discharge review.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of US veterans looking at readmission rates between 2007 and 2013, the 30-day readmission rate was 17.3%, and the 90-day readmission rate was 29.2%. Patients with CD had a higher risk of readmission than UC patients (OR 3.90, 95% CI 1.82-8.90) [26]. For IBD readmissions, predictors that have been reported include opioid use disorder, younger age, mood disorder (depression and/or anxiety), and lack of follow-up visit after hospitalization [26][27][28][29].…”
Section: Robin Dalal and David Schwartzmentioning
confidence: 99%
“…Chronic intestinal inflammation is increasingly recognised due to its implication in the pathogenesis of CRC, which may induce the neoplastic transformation of colonic epithelial cells, promoting cellular proliferation and invasiveness, leading to the infiltration of immune cells and soluble mediators, which eventually provides a favourable microenvironment for tumour initiation and development (Park and Kim 2018;Pejin et al 2017). Accumulating evidence has revealed that patients with inflammatory bowel disease (IBD) are at a high risk of developing CRC (Malhotra et al 2018;Zhou et al 2019). CRC patients are mainly treated with surgery supplemented with other therapeutic options, such as chemotherapy and radiotherapy (Johnson et al 2013;Ganesh et al 2019).…”
Section: Discussionmentioning
confidence: 99%